Diagnostic approach to microcephaly in childhood: a two‐center study and review of the literature. (12th March 2014) - von der Hagen, Maja; Pivarcsi, Mark; Liebe, Juliane; von Bernuth, Horst; Didonato, Nataliya; Hennermann, Julia B; Bührer, Christoph; Wieczorek, Dagmar; Kaindl, Angela M
<x xml:space="preserve">Abstract</x> Aim The aim of this study was to assess the diagnostic approach to microcephaly in childhood and to identify the prevalence of the various underlying causes/disease entities. Method We conducted a retrospective study on a cohort of 680 children with microcephaly (399 males, 281 females; mean age at presentation 7–8mo, range 1mo–5y) from patients presenting to Charité – University Medicine Berlin (n=474) and University Hospital Dresden (n=206). Patient discharge letters were searched electronically to identify cases of microcephaly, and then the medical records of these patients were used to analyze parameters for distribution. Results The putative aetiology for microcephaly was ascertained in 59% of all patients, leaving 41% without a definite diagnosis. In the cohort of pathogenetically defined microcephaly, genetic causes were identified in about half of the patients, perinatal brain damage accounted for 45%, and postnatal brain damage for 3% of the cases. Microcephaly was associated with intellectual impairment in 65% of participants, epilepsy was diagnosed in 43%, and ophthalmological disorders were found in 30%. Brain magnetic resonance imaging revealed abnormalities in 76% of participants. Interpretation Microcephaly remains a poorly defined condition, and a uniform diagnostic approach is urgently needed. A definite aetiological diagnosis is important in order to predict the prognosis and offer genetic counselling. Identifying gene mutations as causes of microcephaly increases our knowledge of brain development and the clinical spectrum of microcephaly. We therefore propose a standardized initial diagnostic approach to microcephaly.